The Effect of Exports and Imports of The Industrial Sector of Foreign Exchange Reserves in Indonesia During The Covid-19 Pandemic - Komi Sinantu Ate; Fanny Nailufar (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This study examined the effect of industrial sector exports and industrial sector imports on foreign exchange reserves in Indonesia during the pandemic. This study used secondary data from January 2020 to January 2022 that was obtained from Bank Indonesia. The method of data analysis used was the Multiple Linear Regression (Ordinary Least Square) model. The results showed that the export of the industrial sector positively and significantly affected foreign exchange reserves in Indonesia, while the import of the industrial sector negatively and insignificant effect on Indonesia's foreign exchange reserves